Meningkatkan Kompetensi Guru melalui Supervisi - Fatimah, Meti; Murtadho, Imam; Nuryahya, Ikhsan (TSAQOFAH, 2026)
Educational supervision is one of the key instruments for improving teachers’ competencies as the primary implementers of instruction, particularly amid curriculum changes, professional demands, and the dynamic development of the educational landscape that requires continuous guidance. This study aimed to conceptually examine the role of educational supervision in enhancing teacher competence. A qualitative approach was employed using a literature study method by reviewing various scholarly sources, such as reference books, journal articles, and relevant education policy documents. The data were analyzed using content analysis techniques by systematically reviewing, comparing, and synthesizing different expert perspectives. The findings indicate that educational supervision plays a crucial role in developing teachers’ pedagogical, professional, social, and personal competencies through structured and reflective guidance. The implementation of effective supervision strategies, such as clinical supervision, collaborative supervision, and the use of technology, supports the creation of more sustainable teacher development processes and leads to improved quality of instructional practice. Thus, educational supervision can be positioned as a strategic instrument for strengthening teacher professionalism and enhancing the quality of learning in educational institutions.